Crystal structure of terazosin hydrochloride dihydrate (Hytrin®), C19H26N5O4Cl(H2O)2. Issue 3 (24th July 2018) - Wheatley, Austin M.; Kaduk, James A.; Vickers, Martin; Gindhart, Amy M.; Sunzeri, Joseph G.; Blanton, Thomas N.
Abstract : The crystal structure of terazosin hydrochloride dihydrate has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Terazosin hydrochloride dihydrate crystallizes in space group P- 1 (#2) with a = 10.01402(4), b = 10.89995(4), c = 11.85357(4) Å, α = 89.5030(3), β = 71.8503(3), γ = 66.5632(2)°, V = 1118.143(8) Å 3, and Z = 2. The terazosin cation occurs in an extended conformation. The crystal structure is dominated by hydrogen bonds. The most notable are the O–H···Cl from the water molecules to the chloride anion and N–H···Cl from the protonated ring nitrogen to the chloride. The amino group donates protons to each of the two water molecules. The powder pattern has been submitted to ICDD ® for inclusion in the Powder Diffraction File™.